Identification of Key Reversible Intermediates in Self‐Reconstructed Nickel‐Based Hybrid Electrocatalysts for Oxygen Evolution - Huang, Jianwen; Li, Yaoyao; Zhang, Yadong; Rao, Gaofeng; Wu, Chunyang; Hu, Yin; Wang, Xianfu; Lu, Ruifeng; Li, Yanrong; Xiong, Jie (Angewandte Chemie International Edition, 2019)
The oxygen evolution reaction (OER) has been explored extensively for reliable hydrogen supply to boost the energy conversion efficiency. The superior OER performance of newly developed non‐noble metal electrocatalysts has concealed the identification of the real active species of the catalysts. Now, the critical active phase in nickel‐based materials (represented by NiNPS) was directly identified by observing the dynamic surface reconstruction during the harsh OER process via combining in situ Raman tracking and ex situ microscopy and spectroscopy analyses. The irreversible phase transformation from NiNPS to α‐Ni(OH)2 and reversible phase transition between α‐Ni(OH)2 and γ‐NiOOH prior to OER demonstrate γ‐NiOOH as the key active species for OER. The hybrid catalyst exhibits 48‐fold enhanced catalytic current at 300 mV and remarkably reduced Tafel slope to 46 mV dec−1, indicating the greatly accelerated catalytic kinetics after surface evolution. An irreversible phase transformation was tracked in situ from NiNPS to α‐Ni(OH)2. This result and potential‐dependent reversible conversion between α‐Ni(OH)2 and γ‐NiOOH prior to OER unveil the real active species of γ‐NiOOH in self‐reconstructed Ni‐based catalysts.